2021
DOI: 10.3390/molecules26237340
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Nanomaterial for Biomedical Imaging of Brain Diseases

Abstract: In the past few decades, brain diseases have taken a heavy toll on human health and social systems. Magnetic resonance imaging (MRI), photoacoustic imaging (PA), computed tomography (CT), and other imaging modes play important roles in disease prevention and treatment. However, the disadvantages of traditional imaging mode, such as long imaging time and large noise, limit the effective diagnosis of diseases, and reduce the precision treatment of diseases. The ever-growing applications of inorganic nanomaterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 141 publications
0
10
0
Order By: Relevance
“…Acidity is a unique hallmark of the tumor microenvironment. Many pH-sensitive nanomedicines were designed and prepared to respond to the acidic tumor microenvironment promoting antitumor efficiency. Inorganic nanomaterials, which possess a diverse range of structure, composition, morphology, and physicochemical properties have been used in cancer treatment and diagnosis as delivery carriers. Recently, various metal oxides or calcium-based nanomaterials have been widely used as pH-sensitive inorganic nanomaterials. It has been reported that ZnO NPs could be used as pH-responsive drug carriers, which possess pH-triggered drug release characteristics displaying a response to acid and a rapid dissolution to Zn 2+ at pH <5.5, especially in lysosomes used for intracellular drug delivery platforms. The intracellular Zn 2+ produced by ZnO NPs has cytotoxic effects in tumor cells. , In addition, ZnO NPs could significantly induce the generation of ROS in tumor cells. In particular, ZnO NPs can make full utilization of disproportional reaction, Haber–Weiss reaction, or Fenton reaction to compensate for O 2 -depletion, thus greatly improving the therapeutic efficacy against hypoxic tumors . ZnO NPs also have good optical properties and high stability to be a promising candidate for bioimaging. , ZnO NPs could be used to in situ upconvert NIR to visible light through the second harmonic generation (SHG) mechanism for tumor imaging. , Recently, we designed an H 2 O 2 -triggered intelligent photodynamic therapy (PDT) nano delivery system, LCL/ZnO, that could selectively regulate the tumor-derived endothelial cells (TECs) and specifically kill tumor cells by producing different singlet oxygen ( 1 O 2 ) in response to different H 2 O 2 gradients in TECs and tumor cells .…”
Section: Introductionmentioning
confidence: 99%
“…Acidity is a unique hallmark of the tumor microenvironment. Many pH-sensitive nanomedicines were designed and prepared to respond to the acidic tumor microenvironment promoting antitumor efficiency. Inorganic nanomaterials, which possess a diverse range of structure, composition, morphology, and physicochemical properties have been used in cancer treatment and diagnosis as delivery carriers. Recently, various metal oxides or calcium-based nanomaterials have been widely used as pH-sensitive inorganic nanomaterials. It has been reported that ZnO NPs could be used as pH-responsive drug carriers, which possess pH-triggered drug release characteristics displaying a response to acid and a rapid dissolution to Zn 2+ at pH <5.5, especially in lysosomes used for intracellular drug delivery platforms. The intracellular Zn 2+ produced by ZnO NPs has cytotoxic effects in tumor cells. , In addition, ZnO NPs could significantly induce the generation of ROS in tumor cells. In particular, ZnO NPs can make full utilization of disproportional reaction, Haber–Weiss reaction, or Fenton reaction to compensate for O 2 -depletion, thus greatly improving the therapeutic efficacy against hypoxic tumors . ZnO NPs also have good optical properties and high stability to be a promising candidate for bioimaging. , ZnO NPs could be used to in situ upconvert NIR to visible light through the second harmonic generation (SHG) mechanism for tumor imaging. , Recently, we designed an H 2 O 2 -triggered intelligent photodynamic therapy (PDT) nano delivery system, LCL/ZnO, that could selectively regulate the tumor-derived endothelial cells (TECs) and specifically kill tumor cells by producing different singlet oxygen ( 1 O 2 ) in response to different H 2 O 2 gradients in TECs and tumor cells .…”
Section: Introductionmentioning
confidence: 99%
“…The inorganic nanomaterial is used in the designing the novel imaging systems. The nanomaterials used in targeting the diseases can be improved via surface modification or fusing with functional materials for betterment of the targeting property [7]. Fluorescent probes are utilized in fluorescence imaging (FL) by labeling specific cells or molecules to generate fluorescence signal via excitation of external light.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent probes are utilized in fluorescence imaging (FL) by labeling specific cells or molecules to generate fluorescence signal via excitation of external light. It is involved in varied applications owing to less expenses, convenient operation, intrinsic biological safety of the imaging and quantitative sensitivity on the biological imaging grounds [7]. The existing contrast agents used in the imaging technique have the certain drawbacks like weak and short life, difficulty in maintaining high MRI resolution and fast weakening of MRI enhancement signal in the body, side effects due to improper dose.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations